Program Leniency w unijnym prawie ochrony konkurencji - Szwedziak, Ilona (Kwartalnik Prawa Publicznego, 2012)
The main purpose of this article is to bring the essence of construction established for the need of consumer and competition protection law, namely the mitigation of fines programme, also known as Model Leniency Programme. This elaboration is focused on strictly European mechanism, which influences the competition law regulations in many EU countries. In particular the main focus was put on basic assumptions of Leniency and its two dimensions: immunity from fines and reduction of fines in cartel cases. Further on the author described procedural aspects of Leniency programme functioning. In addition the emphasis was put on the significant impact which Leniency has in efficient introduction of competition policies, especially in fights against cartels, which are taken as the most harmful.